2016
DOI: 10.1080/09540121.2016.1198749
|View full text |Cite
|
Sign up to set email alerts
|

Fate control and well-being in Chinese rural people living with HIV: mediation effect of resilience

Abstract: Fate control has been often misconceptualized as a superstitious belief and overlooked in health psychology. It is not known how this cultural belief might impact the well-being of Chinese people living with HIV. This study examined the protective role of fate control for well-being and the potential mediation effect of resilience. Participants in this study were rural patients who contracted HIV via commercial blood donation. In this cross-sectional survey, 250 participants completed measures of fate control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(37 reference statements)
2
3
0
Order By: Relevance
“…The results of correlation analysis indicated that the study variables have significant correlations with each other (see table 2). The results are consistent with the study of Yu et al 19 fate control is an internal control state that works as cognitive defense mechanism, it reduces self-blaming by increasing rationalization about the disease in the patients that increase wellbeing. Furthermore, a significant association was examined between hardiness, resilience and wellbeing, because hardiness focuses more on endurance in a critical health situation, whereas resilience is the capacity to recover after the adverse situation the results of present study coincides with the existing literature in the west.…”
Section: Discussionsupporting
confidence: 92%
“…The results of correlation analysis indicated that the study variables have significant correlations with each other (see table 2). The results are consistent with the study of Yu et al 19 fate control is an internal control state that works as cognitive defense mechanism, it reduces self-blaming by increasing rationalization about the disease in the patients that increase wellbeing. Furthermore, a significant association was examined between hardiness, resilience and wellbeing, because hardiness focuses more on endurance in a critical health situation, whereas resilience is the capacity to recover after the adverse situation the results of present study coincides with the existing literature in the west.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings highlight the protective role of external resilience resources in PLWHA in a rural area of China. Although our study replicated the previous reports on the benefits of individual resilience resources in this population (Yu, Zhang, Chow, et al, 2016;Zhang et al, 2015), the roles of marital and family relationships as external resilience factors for Chinese PLWHA were neglected in previous studies because they are often described as an isolated population that brings stigma to their close family members (Cao, Sullivan, Xu, & Wu, 2006;Li et al, 2008). Resilience literature has suggested the importance of close relationships in the resilience process (Fergus & Zimmerman, 2005;Masten, 2016;Yates & Masten, 2004), which has been supported in people affected by non-stigmatized chronic diseases such as cancer and renal disease (Pruchno et al, 2009;Rosland & Piette, 2010;Rottmann et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…For individual resilience resources, summarized previous findings about the personal characteristics of resilient people and subsequently developed the Connor-Davidson Scale of Resilience to provide a general measure of individual resilience resources, which covers resilient personal qualities such as self-efficacy and acceptance of change. These individual resilience resources have been found to be associated with better adjustment in various at-risk populations (Connor, Davidson, & Lee, 2003;Pietrzak, Johnson, Goldstein, Malley, & Southwick, 2009;Zhang, Yu, Zhou, & Zhang, 2017), including PLWHA in China (Yu, Chen, Ye, Li, & Lin, 2016;Yu, Zhang, Chow, Chan, & Chan, 2016;Zhang et al, 2015). Resilience resources are also external to individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In a large-scale community study in Romania, Dinca and Iliesca [40] found that people high in fate control reported more health-protective behaviors, including higher medication intake and more visitations to doctor than those low in fate control, despite the same reported health conditions. In another study on fate control and well-being among HIV patients, fate control was positively related to resilience, which in turn positively predicted well-being [54].…”
Section: Fate Control Can Also Induce Adaptive Copingmentioning
confidence: 94%